2012
DOI: 10.1055/s-0031-1298866
|View full text |Cite
|
Sign up to set email alerts
|

Kopfverletzungen: Mortalität, Verletzungsmuster, Intubationshäufigkeit

Abstract: Zusammenfassung Penetrierende Schussverletzungen des Kopfes sind in Europa bisher selten. Aufgrund zunehmender Kriminalit?t und Terror muss mit einer Zunahme der penetrierenden Verletzungen des Kopfes gerechnet werden. In dieser Arbeit zeigen wir Unterschiede bei Intubationsraten im Rettungsdienst bzw. Schockraum bei Patienten mit stumpfem Kopftrauma (31,4?%) bzw. nach Schussverletzungen des Kopfes (52,5?%) auf. Es finden sich deutliche Unterschiede in der Mortalit?t nach Verkehrsunfall (8,3?%) und nach Schuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…An analysis of emergency data from the Chris Hani Baragwanath Academic Hospital (CHB) in Johannesburg, South Africa, was used to provide an example of typical injuries after stabbing and gunshot wounds. This analysis showed that, among stabbing injuries, thoracic injuries were the most common (44.4%), whereas among gunshot injuries, abdominal injuries dominated (34.4%) and thoracic injuries came second (24.8%) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of emergency data from the Chris Hani Baragwanath Academic Hospital (CHB) in Johannesburg, South Africa, was used to provide an example of typical injuries after stabbing and gunshot wounds. This analysis showed that, among stabbing injuries, thoracic injuries were the most common (44.4%), whereas among gunshot injuries, abdominal injuries dominated (34.4%) and thoracic injuries came second (24.8%) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge is to transport patients with penetrating injuries to appropriate hospitals that can adequately care for these injury patterns [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%